The Global Financial Crisis: Analysis and Policy Implications - Nanto, Dick K. (2009)
The world has entered a global recession that is causing widespread business contraction, increases in unemployment, and shrinking government revenues. Some of the largest and most venerable banks, investment houses, and insurance companies have either declared bankruptcy or have had to be rescued financially. Nearly all industrialized countries and many emerging and developing nations have announced economic stimulus and/or financial sector rescue packages, such as the American Recovery and Reinvestment Act of 2009 (P.L. 111-5). Several countries have resorted to borrowing from the International Monetary Fund as a last resort. The crisis has exposed fundamental weaknesses in financial systems worldwide, demonstrated how interconnected and interdependent economies are today, and has posed vexing policy dilemmas. The process for coping with the crisis by countries across the globe has been manifest in four basic phases. The role for Congress in this financial crisis is multifaceted. While the recent focus has been on combating the recession, the ultimate issue perhaps is how to ensure the smooth and efficient functioning of financial markets to promote the general well-being of the country while protecting taxpayer interests and facilitating business operations without creating a moral hazard. In addition to preventing future crises through legislative, oversight, and domestic regulatory functions, Congress plays a key role in generating policy options and informing the public. On the regulatory side, the largest questions seem to be how U.S. regulations should be changed and, if changed, how closely those changes are to be harmonized with international recommendations. Congress also plays a role in measures to reform and recapitalize the International Monetary Fund, the World Bank, and regional development banks. On June 17, 2009, the Department of the Treasury presented the Obama Administration proposal for financial regulatory reform. CRS Report for Congress.